Variation in Indonesian cocoa farm productivity in relation to management, environmental and edaphic factors. (12th October 2020) - Daymond, A. J.; Prawoto, A.; Abdoellah, S.; Susilo, A.W.; Cryer, N. C.; Lahive, F.; Hadley, P.
Abstract: A survey was conducted of Indonesian cocoa farms to assess the extent of yield variation and factors associated with this variation. The survey of 120 farms during the course of 3 years encompassed four provinces in Sulawesi (South, South-East, West and Central), Western Sumatra, Lampung, East Java and West Papua. A high degree of yield variation was observed between farms, the average over 3 years ranged from 39 to 3586 kg ha −1 . Overall, yields were greater on farms that were classified as 'highly managed', compared to 'moderately' and 'less managed'. Seasonal variability in yields was generally greater in districts with a more pronounced dry season such as South Sulawesi and Lampung. Multiple regression analyses revealed particular husbandry practices that were linked with higher cocoa yields. Specifically, the use of inorganic fertilisers, application of fungicides against blackpod and weeding were all practices that were associated with higher yields. A positive association between rainfall and yield was observed for the years 2014/15 and 2015/16 but not 2016/17, which was a La Niña year (when rainfall totals were higher). Some of the farms surveyed were planted with cocoa at very low densities implying an opportunity for yield improvement through gap filling or replanting at higher densities (although it was noted that some farmers maintained lower planting densities due to the cultivation of companion crops). Given the smallholder status of most cocoa farms in Indonesia (mean area in this study was 0.71 ha) it is important that farmers are able to maximise returns from their land in order to maintain a livelihood. This study illustrated the potential for yield improvement on Indonesian cocoa farms through adoption of best agronomic practice.